Revisiting Phryma leptostachya L.: phylogenetic relationships and biogeographical patterns from complete plastome - Yeseul Kim; Sumin Jeong; Inkyu Park; Hye-Kyoung Moon (BMC Plant Biology)
Abstract Background Phryma leptostachya L. is a notable example of a species with a disjunct distribution, found in both East Asia and Eastern North America. Despite the striking morphological similarities between these geographically isolated populations, molecular evidence suggests that they may have diverged sufficiently to be considered distinct taxa. Results To clarify this, we analyzed the plastomes of P. leptostachya from Korea, Russia, and the USA. Their sizes ranged from 152,974 to 153,325 bp, each containing 113 genes. Differences were observed in the boundaries between large single copy (LSC)/IRa and IRb/LSC. In P. leptostachya_USA, the rps19 gene extended 30–31 bp into the IRa, and the rpl2 gene contracted 51–53 bp at the IRa/b compared to those of P. leptostachya_Korea and P. leptostachya_Russia, suggesting that expansion of the inverted repeat (IR) region occurred in P. leptostachya_USA. Regions such as psbZ-trnG, ccsA-ndhD, petA-psbJ, and psbC-trnS were identified as hotspots with sequence differences in the plastome, indicating differences among P. leptostachya variants. Phylogenetic analysis showed that P. leptostachya from Korea and Russia formed monophyletic groups, while the variety from the USA was paraphyletic. The divergence of P. leptostachya_USA occurred during the Pliocene, about 5.25 million years ago (MYA), whereas the split between P. leptostachya_Korea and P. leptostachya_Russia is estimated to have occurred approximately 0.87 MYA during the Pleistocene. The results also reveal that the family Phrymaceae underwent multiple dispersal and vicariance events from North America to East Asia, offering key insights into the phylogenetic relationships between P. leptostachya populations from Korea, Russia, and the USA. Based on the evidence, it is likely that P. leptostachya originated in North America and later migrated to East Asia via the Russian Far East and the Bering Land Bridge. Conclusions In conclusion, our study demonstrates clear molecular differences among P. leptostachya populations from various geographic locations, suggesting that these populations should be recognized as distinct species rather than conspecifics.